Evaluation of chondroprotective activity of Channa striatus in rabbit osteoarthritis model - Abdul Kadir, Azidah; Abdul Kadir, Arifah; Abd Hamid @ Abdul Razak, Roslida; Mat Jais, Abdul Manan; Omar, Julia; Sadagatullah, Abdul Nawfar; Badrin, Salziyan; Win, Thin Thin; Sirajudeen, K. N. S.; Salleh, Annas (Hindawi, 2019)
Objectives The objective of the study is to evaluate the chondroprotective activity of Channa striatus (Channa) and glucosamine sulphate (glucosamine) on histomorphometric examinations, serum biomarker, and inflammatory mediators in experimental osteoarthritis (OA) rabbit model.